Pengaruh Perceived Organizational Support and Work Engagement Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Mediasi pada UMKM Kasongan, Bantul, Yogyakarta - Efrat Tirta Wijaya; Sri Rahayu; Ra Vidia Gati (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of Perceived Organizational Support (POS) and Work Engagement on employee performance with organizational commitment as a mediating variable at SMEs in Kasongan, Bantul, Yogyakarta. This research was motivated by the importance of improving employee performance in the SME sector, which still faces various challenges, such as low employee engagement, suboptimal organizational support, and weak organizational commitment. This study employed a quantitative approach using a survey method. The population of this research consisted of employees working in SMEs in Kasongan, Bantul, Yogyakarta. The sampling technique used was purposive sampling with a total of 150 respondents. Data were collected through questionnaires using a Likert scale. The data analysis method used was Structural Equation Modeling based on Partial Least Square (SEM-PLS). The results showed that Perceived Organizational Support had a positive and significant effect on employee performance. However, Work Engagement did not have a significant direct effect on employee performance. In addition, Perceived Organizational Support and Work Engagement were found to have a positive and significant effect on organizational commitment. Organizational commitment also had a positive and significant effect on employee performance. The mediation test results indicated that organizational commitment partially mediated the effect of Perceived Organizational Support on employee performance and fully mediated (full mediation) the effect of Work Engagement on employee performance. This study implies that improving organizational support and strengthening organizational commitment are important strategies for enhancing employee performance in the SME sector, particularly in SMEs in Kasongan.